Nursing, Citizenship and Gender Reality in Chile [la Enfermería, Realidad de Ciudadanía y de Género en Chile] - Pavez-Lizarraga, A (2013)
This reflection aims to addresses the identity of nursing in the context of citizenship and gender. It describes the importance of the three aspects: identity, citizenship and gender, in the social construction of reality. Nursing as a discipline and profession is subject to the meaning of these concepts, being simultaneously a manifestation of the relationship and the balance existing between the factual and symbolic reality. We conclude on the importance of the consolidation of nursing in the dynamics of the contemporary society where caring emerge as a societal problem that oversteps the private and the feminine world.